TOWARDS AN EMPOWERED WOMANHOOD: Blessed Kuriakose Elias Chavara’s Socio- Pastoral Vision of Women and the Founding and Growth of the Congregation of the Mother of Carmel - Maria, Navya (Asian Horizons, 2013)
Empowerment as a term applied to human beings refers to increasing the spiritual, social, political, educational, cultural, gender and economic calibre of individuals or groups of individuals. Gender empowerment in Indian culture almost always points to empowerment of women. The dream of liberating women can come true only when every section of the society is free from gender bias and advocates improvement of the status of women in the society. In order to empower women, the society needs to adopt an integrated approach towards uplifting women and bringing them into the mainstream of national development. However, the present position and status of women in the Indian society in general, and the rural society in particular are still not satisfactory.